3x-y=-2

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 3x from both sides of the equation.

-y=-2-3x

Multiply each term in -y=-2-3x by -1

Multiply each term in -y=-2-3x by -1.

(-y)⋅-1=(-2)⋅-1+(-3x)⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=(-2)⋅-1+(-3x)⋅-1

Multiply y by 1.

y=(-2)⋅-1+(-3x)⋅-1

y=(-2)⋅-1+(-3x)⋅-1

Simplify (-2)⋅-1+(-3x)⋅-1.

Simplify each term.

Multiply -2 by -1.

y=2+(-3x)⋅-1

Multiply -1 by -3.

y=2+3x

y=2+3x

Reorder 2 and 3x.

y=3x+2

y=3x+2

y=3x+2

y=3x+2

Rewrite in Slope-Intercept Form 3x-y=-2